ANALISIS POTENSI DAN TINGKAT PEMANFAATAN SUMBERDAYA IKAN DI PERAIRAN KABUPATEN BANGKA SELATAN - Dersi Heka Mayu; Kurniawan Kurniawan; Arief Febrianto (Jurnal Perikanan Tangkap : Indonesian Journal of Capture Fisheries, 2018)
Marine fishery resources consist of pelagic fish and demersal fish. The area of marine fisheries management in South Bangka Regency has enormous potential because it is facing directly with the high seas. The purpose of this study is to know the potential and the utilization rate of marine fishery in South Bangka Regency for the development of marine fishery sector in the future with attention to resource sustainability. This study was conducted from December 2017 to January 2018. Data was taken secondary data. Data analysis is the method of Maximum Sustainable Yield (MSY) Schaefer model and Utilization Rate. The results showed MSY small pelagic fish 31,630 ton / year with Fopt 88,097 trip / year, large pelagic fish 2,340 ton / year with (Fopt) 127.465 trip / ton while demersal fish MSY value 16,750 ton / year with Fopt of 244,812 trips / ton, this indicates that fish resources in the waters of South Bangka Regency have not yet reached overfishing, but by 2014 the value of MSY and Fopt of large pelagic fish compared to production value and fishing effort has exceeded MSY and (Fopt) while small pelagic fish and demersal in 2014, the value of fishing effort has exceeded the optimum F. Level of fish resource utilization in South Bangka Regency, average utilization rate in 2012-2016 small pelagic fish equal to 71,62% mean is optimum level, average of pelagis big pelagis utilization rate equal to 89,19%, mean is optimum level and the average demersal fish utilization rate of 64.07%, means it is at a medium level.Keywords : Potential, Utilization, Fish Resources, South Bangka Regency